An "Ecosystem of Entrepreneurialisation"? An interpretative approach to the transformation of the third Sector - Esposto, Edoardo; Ficcadenti, Cecilia (PARTECIPAZIONE E CONFLITTO, 2020)
Since the early 2000s scholars have observed a tendency, within the third sector, to combine social values and market objectives in new hybrid configurations. This entrepreneurial turn of non-profit organisations (NPOs) has intersected another historical trajectory of change: their integration in the provision and governance of human and social services. The research contributes to the debate on the transformation of the third sector by addressing the relationship between these two trajectories of change. An interpretative tool is devised, drawing upon public policy research and new discursive institutionalism. To exemplify the interpretative approach, a case study of social entrepreneurship rooted in southern Italian local communities is explored. The research helps building an explanation of the transformation of the third sector centred on the evolving and interactive policy context in which NPOs are embedded, presently resembling an "ecosystem of entrepreneurialisation".